Narasi dan Wacana Komunikasi Politik Prabowo–Gibran dalam Kontestasi Pemilu 2024 - Siti Rohmah; Meriwijaya . (Universitas Islam Negeri (UIN) Salatiga, 2025)
Social media has transformed into a primary arena for shaping public opinion and political image in the digital era. This study aims to examine the narrative construction and discourse of the Prabowo-Gibran political communication pair in the 2024 election contest. This study is based on political communication theory, which highlights how symbols, language, and representation shape public perception. The method used is a qualitative content analysis approach, through tracing messages and symbols that appear on Prabowo and Gibran's personal social media channels, such as TikTok, Instagram, and YouTube channels, accompanied by reading netizen responses and online media coverage. The results of the study show that the Prabowo-Gibran pair implemented a digital populism-based communication strategy by combining humor, emotional closeness, and digital technology. The